Boron adsorption in lowland soils from Parana State, Brazil - Steiner, Fabio [UNESP] (2012)
Boron adsorption by soil is the main phenomenon that affects its availability to plants. This, the present study investigated the effect of liming on B adsorption by lowland soils of Parana State, and to correlate these values with the physical and chemical properties of the soils. Surface samples of three lowland soils [Gleissolo Haplico (GX), Plintossolo Haplico (FX) and Cambissolo Haplico (CX)], with different origin material and physicochemical properties were used. Samples with or without liming application were incubated during 60 days. Boron adsorption was accomplished by shaking 4.0g soil samples, for 24 h, with 20 mL of 0.01 mol L-1 CaCl2 solution containing different concentrations of B (0, 1, 2, 4, 8 and 16 mg L-1). Sorption was fitted to non-linear form of the Langmuir adsorption isotherm. The adsorption isotherms indicated that the B adsorption increased with its increasing concentration in the equilibrium solution. Maximum adsorption capacity of B ranged from 3.0 to 13.9 mg kg(-1) (without liming) and 14.7 to 35.7 mg kg(-1) (with liming). Liming increased the amount of adsorbed B in Gleissolo Haplico and Plintossolo Haplico soils, although the bonding energy has decreased. The amount of adsorbed B by Cambissolo Haplico soil was not affected by liming application. The most important soil properties affecting the B adsorption in lowland soils were pH, clay content, exchangeable aluminum and iron oxide contents.